Worldview measures of assessment of evidence in a constitutional litigation - Shaptala, Nataliya K. (Journal of the Belarusian State University. Law, 2019)
The article is devoted to the study of the philosophical and legal content of worldview dimensions of the assessment of evidence in the constitutional court process, and the understanding of their role in relation to the adoption of a fair and well-founded judicial decision. The author pays special attention to issues related to the definition of general principles of philosophical and functional specificity of evidence in the work of the body of constitutional jurisdiction and their influence on the paradigm of regulation of social relations in the main spheres of social activity of society.